English Writing Development through Local Wisdom-Integrated Suggestopedia and Digital Portfolio Assessment: Evidence from a Repeated Measures Study - Riyadi Saputra; Yenni Rozimela; Syahrul Ramadhan (Dharmas Education Journal (DE_Journal), 2026)
Writing is one of the most challenging skills for EFL students due to difficulties in generating ideas, organizing texts, and revising written work effectively. This study aimed at examiningg the development of students’ English writing skills through the integration of Local Wisdom-Integrated Suggestopedia and Digital Portfolio Assessment. A quantitative approach with a One-Group Repeated Measures Design was employed involving 14 undergraduate students of an English Education Study Program. Writing performance was measured at four points: before the intervention (T1), during the intervention (T2), one month after the intervention (T3), and two months after the intervention (T4). Data were analyzed using descriptive statistics, Repeated Measures ANOVA, and Bonferroni pairwise comparisons. The results revealed a consistent improvement in writing performance, with mean scores increasing from 65.57 (T1) to 75.43 (T2), peaking at 83.57 (T3), and remaining high at 79.36 (T4). Repeated Measures ANOVA indicated a significant difference across the four measurements, F(1.098, 14.279) = 28.827, p < .001. The findings demonstrate that the intervention effectively improved and sustained students’ writing development. Pedagogically, integrating local wisdom, Suggestopedia, and digital portfolio assessment provides a culturally relevant, low-anxiety, and process-oriented approach to enhancing EFL writing instruction